An empirical analysis of the impact of floating exchange rate on balance of payment in Nigeria (1986 - 2016) - GATAWA, N. M.; ELIJAH, Sunday; UMAR, Mohammed (Turkish Economic Review, 2018)
Abstract. This paper empirically investigates the impact of floating exchange rate on balance of payment in Nigeria during 1986 – 2016. Unit root test, cointegration test, VEC Granger causality/Exogeneity Wald test and Vector Error Correction Model (VECM) were econometric tools used to establish the relationship between exchange rate and balance of payment. The results showed a positive and statistically significant relationship in both short-run and long-run between balance of payment and exchange rate of the Nigerian Economy during the period under review. The VEC Granger Causality/Block Exogeneity further revealed that the major determinants of exchange rate are real GDP and money supply. It further reveals that the nexus among the variables runs from government expenditure to real GDP and money supply to exchange rate, and then to Balance of Payment. Therefore it was recommended amongst other things that the policy of exchange rate depreciation should be maintained but with government intervention guide. Government through Central Bank of Nigeria (CBN) should apply expenditure reducing monetary policies through money supply and domestic credit to promote favourable BOT which invariably stabilizes BOP. Keywords. Floating exchange rate, Balance of payments, VECM. JEL. F10, F30, F31.